2021
DOI: 10.3390/molecules26030528
|View full text |Cite
|
Sign up to set email alerts
|

Crocins, the Bioactive Components of Crocus sativus L., Counteract the Disrupting Effects of Anesthetic Ketamine on Memory in Rats

Abstract: Consistent experimental evidence suggests that anesthetic doses of the non-competitive N-methyl-d-aspartate (NMDA) receptor antagonist ketamine cause severe memory impairments in rodents. Crocins are among the various bioactive ingredients of the plant Crocus sativus L., and their implication in memory is well-documented. It has not yet been elucidated if crocins are able to attenuate the memory deficits produced by anesthetic ketamine. The present study was undertaken aiming to clarify this issue in the rat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In preclinical models, spatial memory is a type of cognitive ability that can be assessed in preclinical models through behavioral tests such as the MWM or the Y-maze (Terry et al , 2009; Kraeuter et al , 2019). Acute or repeated administration of KET has been reported to be capable of inducing learning and memory consolidation impairment, linked to various neurochemical changes related to spatial memory in both cognitive models (Trofimiuk et al 2018; Turktan et al , 2019; Pitsikas et al , 2021). For example, exposure to this agent can cause a reduction in serum and hippocampal levels of brain-derived neurotrophic factor (Li et al , 2020; Meng et al , 2020) and increases AKT and ERK phosphorylation in this brain structure (Meng et al , 2020; Shi et al , 2020).…”
Section: Spatial Working Memory and Ket: Morris Water Maze T And Y-mazesmentioning
confidence: 99%
“…In preclinical models, spatial memory is a type of cognitive ability that can be assessed in preclinical models through behavioral tests such as the MWM or the Y-maze (Terry et al , 2009; Kraeuter et al , 2019). Acute or repeated administration of KET has been reported to be capable of inducing learning and memory consolidation impairment, linked to various neurochemical changes related to spatial memory in both cognitive models (Trofimiuk et al 2018; Turktan et al , 2019; Pitsikas et al , 2021). For example, exposure to this agent can cause a reduction in serum and hippocampal levels of brain-derived neurotrophic factor (Li et al , 2020; Meng et al , 2020) and increases AKT and ERK phosphorylation in this brain structure (Meng et al , 2020; Shi et al , 2020).…”
Section: Spatial Working Memory and Ket: Morris Water Maze T And Y-mazesmentioning
confidence: 99%
“…Crocin attenuates schizophrenia-like behavioral disruptions caused by the NMDAR antagonist ketamine in rats (Georgiadou et al ., 2014). It has also been suggested that the modulatory role of crocin in the extracellular signal-regulated protein kinase (ERK) pathway and c -fos expression together with its potent antioxidant activities might be critical for counteracting the amnestic effects of anesthetic ketamine (Pitsikas and Tarantilis, 2021). There is sufficient evidence that natural herbal medicines can produce antidepressant effects by regulating the levels of glutamate and NMDAR subunits in the frontal cortex and hippocampus (Lou et al ., 2010; Shin et al ., 2014; Zhang et al ., 2016; Ren and Chen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Four articles report novel findings on the effects of saffron and its ingredients on neuropsychiatric disorders. In the first of two articles, Pitsikas and Tarantilis report the beneficial effects of crocins on memory loss, induced by the widely used anesthetic ketamine, in rats [ 7 ]. In the second article, the same authors find that the anxiolytic properties of crocins are mediated by their agonistic action on the GABA A -benzodiazepine receptor [ 8 ].…”
mentioning
confidence: 99%